1988
DOI: 10.1001/jama.1988.03720140023028
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Grade A Eggs as a Major Source of Salmonella enteritidis Infections

Abstract: From 1976 to 1986, reported Salmonella enteritidis infections increased more than sixfold in the northeastern United States. From January 1985 to May 1987, sixty-five foodborne outbreaks of S enteritidis were reported in the Northeast that were associated with 2119 cases and 11 deaths. Twenty-seven (77%) of the 35 outbreaks with identified food vehicles were caused by Grade A shell eggs or foods that contained such eggs. National data from 1973 to 1984 showed that S enteritidis outbreaks (44%) were more freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(35 citation statements)
references
References 19 publications
2
31
0
2
Order By: Relevance
“…This serotype is among the most common pathogens of chickens that could also adversely affect human health following exposure to infected or contaminated chicken products 18,30 . Furthermore it can also cause serious disease in other livestock species such as cattle and sheep.…”
Section: Discussionmentioning
confidence: 99%
“…This serotype is among the most common pathogens of chickens that could also adversely affect human health following exposure to infected or contaminated chicken products 18,30 . Furthermore it can also cause serious disease in other livestock species such as cattle and sheep.…”
Section: Discussionmentioning
confidence: 99%
“…The complete ELISA allowed us to potentially detect all prevalent serovars isolated on French pig farms belonging to the B, E1, C1, or C2 groups, because it was based on the somatic antigens (O : 1,3,5,6,7,8,9,10,12). In comparison, theoretically 95% of Salmonella serovars occurring in Danish pigs are detectable with the mix-ELISA based on S. Typhimurium (O : 1, 4, 5, 12) and Choleraesuis antigens (O : 6, 7) developed by Nielsen et al [14] in Denmark [1].…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been well established that poultry is a major source of food-poisoning caused by Salmonella [12], pork also contributes to human infections [13,19]. ELISA is a valuable tool to detect infected pigs [14] because it is inexpensive and rapid compared with the bacteriological method.…”
Section: Introductionmentioning
confidence: 99%
“…Over 70% of the infections were traced to foods containing grade 'A' eggs. In 1990, according to the World Health Organization (WHO) found that from 1979 to 1987, incidents of salmonella had increased in 24 of 35 nations under surveillance including Spain, Hungary, France, Norway and the USA (Lane et al, 2014;Poppe, 1999;Rodrigue et al, 1990;St. Louis et al, 1988).…”
Section: Salmonella In England and Walesmentioning
confidence: 99%